Omnichannel Integration in Beauty Retail: Its Impact on Consumer Shopping Experience: Case Study of Sociolla - Sari, Mulyana; Khairina Rosyadah (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The rapid digital transformation in the retail industry has encouraged businesses to adopt omnichannel strategies to enhance the consumer shopping experience. This study examines the impact of omnichannel integration, online and offline channel synchronization, and key influencing factors on the consumer shopping experience in the beauty retail industry, with Sociolla as a case study.This research employs a quantitative approach, using primary data collected through an online survey distributed to Sociolla consumers. The study analyzes the relationship between Omnichannel Strategy, Online and Offline Integration, and Factors Influencing Consumer Shopping Experience on Consumer Shopping Experience at Sociolla. The findings indicate that these factors play a crucial role in shaping consumer perceptions and satisfaction when shopping in an omnichannel environment.The results confirm that a well-executed omnichannel strategy, seamless online and offline integration, and a personalized shopping experience significantly enhance consumer shopping satisfaction. This study highlights the growing importance of integrating digital and physical retail experiences in the beauty industry to meet evolving consumer expectations.